AN ANALYSIS OF MEANINGS OF EUPHEMISM USED BY SIKKA KROWE ETHNIC IN HABI VILLAGE SIKKA REGENCY - Genoveva Dua Eni (Postgraduate School, Universitas Nusa Cendana, 2018)
The present research is about the meaning of euphemism used by Sikka Krowe ethnic in Habi village Sikka regency. There are two problems to be answered in this writing, namely what are the meanings of the euphemism used by Sikka Krowe ethnic in Habi village? and why people of Sikka Krowe Ethnic who live in Habi village use Euphemism?. The aims of this study are to describe the meanings of the euphemism used by Sikka Krowe ethnic in Habi village and to describe the reasons of Sikka Krowe ethnic who live in Habi village use the euphemism. This study used a descriptive method. Descriptive method is used to describe or to define the condition of the object or subject of the research. The data was gathered through observation and interview. The result of the research show that (1) there are two types of meaning namely conceptual meaning and associative meaning, (2) in terms of the reason why people of Sikka Krowe ethnic used euphemism, there are two reasons of the using of euphemism in Sikka Krowe ethnic. First is because the speaker wants to talk politely and the second is because the speaker wants to escape their self from the dangerous thing of speaks the taboo or forbidden things directly.